2021
DOI: 10.1097/ede.0000000000001328
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Opioid Analgesics and the Risk of Adverse Birth Outcomes

Abstract: Background: It is unclear whether confounding accounts for the increased risk of preterm birth and small for gestational age (SGA) birth in opioid analgesic exposed pregnancies. Methods: Using universal coverage health data for Ontario, we assembled a cohort of mother-infant pairs without opioid use disorder (627,172 pregnancies and 509,522 women). We estimated risk ratios (RRs) between opioid analgesics and preterm birth, SGA birth, and stillbirth; neonatal abstinence syndrome was a secondary outcome. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 31 publications
(55 reference statements)
2
42
0
Order By: Relevance
“…Many have a history of severe mental illness and non-opioid substance use. Women using opioids for pain are less likely to have the same degree of socio-economic disadvantages than those on OAT, but are still at a higher risk than the general population (Camden et al 2021). Using data from both Ontario and England, UK, we have shown that 1 in 20 mothers of infants with NAS die within 10 years of delivery, which represents greater than a 10-fold increased risk compared with other mothers (Guttmann et al 2019).…”
Section: Prenatal Opioid Exposure and Maternal Healthmentioning
confidence: 85%
See 4 more Smart Citations
“…Many have a history of severe mental illness and non-opioid substance use. Women using opioids for pain are less likely to have the same degree of socio-economic disadvantages than those on OAT, but are still at a higher risk than the general population (Camden et al 2021). Using data from both Ontario and England, UK, we have shown that 1 in 20 mothers of infants with NAS die within 10 years of delivery, which represents greater than a 10-fold increased risk compared with other mothers (Guttmann et al 2019).…”
Section: Prenatal Opioid Exposure and Maternal Healthmentioning
confidence: 85%
“…Opioid use in pregnancy -including therapeutic use for pain management, treatment of opioid use disorder (OUD) and non-medical use of illegally obtained opioidshas increased dramatically over the past two decades in North America (Brogly et al 2017;Haight et al 2018). Approximately 1 in 20 (5.3%) infants born in Ontario have prenatal opioid exposure (POE), with higher rates in those whose mothers are younger and from low-income neighbourhoods or rural areas (Camden et al 2021). High rates (30%) have been documented in First Nations communities in Northwest Ontario (Dooley et al 2018).…”
Section: The Issuementioning
confidence: 99%
See 3 more Smart Citations